First genetic linkage map of Lathyrus cicera based on RNA sequencing-derived markers: Key tool for genetic mapping of disease resistance. Issue 1 (1st September 2018) - Santos, Carmen; Almeida, Nuno Felipe; Alves, Mara Lisa; Horres, Ralf; Krezdorn, Nicolas; Leitão, Susana Trindade; Aznar-Fernández, Thaïs; Rotter, Björn; Winter, Peter; Rubiales, Diego; Vaz Patto, Maria Carlota
Abstract: The Lathyrus cicera transcriptome was analysed in response to rust ( Uromyces pisi ) infection to develop novel molecular breeding tools with potential for genetic mapping of resistance in this robust orphan legume species. One RNA-seq library each was generated from control and rust-inoculated leaves from two L. cicera genotypes with contrasting quantitative resistance, de novo assembled into contigs and sequence polymorphisms were identified. In toto, 19, 224 SNPs differentiate the susceptible from the partially resistant genotype's transcriptome. In addition, we developed and tested 341 expressed E-SSR markers from the contigs, of which 60.7% varied between the two L. cicera genotypes. A first L. cicera linkage map was created using part of the developed markers in a RIL population from the cross of the two genotypes. This map contains 307 markers, covered 724.2 cM and is organised in 7 major and 2 minor linkage groups, with an average mapping interval of 2.4 cM. The genic markers also enabled us to compare their position in L. cicera map with the physical position of the same markers mapped on Medicago truncatula genome, highlighting a high macrosyntenic conservation between both species. This study provides a large new set of genic polymorphic molecular markers with potential for mapping rust resistances. It represents the first step towards genomics-assisted precision breeding in L. cicera . Legumes: Tools for mapping genes for rust resistance: Genetic analysis of Lathyrus cicera, or 'chickling pea', a plant most commonly cultivated for animal feed, identified DNA polymorphisms that may be associated to resistance to the fungal disease known as rust. Researchers in Europe led by Maria Carlota Vaz Patto at the NOVA University of Lisbon, Portugal, discovered thousands of genetic differences between plants that were either susceptible to or at least partially resistant to the rust fungus Uromyces pisi . They created a 'genetic linkage map', which reveals the likelihood that different genetic characteristics will be inherited together through the generations. This map can now serve as a tool to help geneticists and plant breeders understand and promote resistance to rust and potentially other fungal diseases in L cicera . The results may also be applied to other legumes, including peas and beans more commonly cultivated for human consumption.